Anti‐adipocyte antibody response in patients with non‐alcoholic fatty liver disease. Issue 5 (May 2015) - Karrar, Azza; Stepanova, Maria; Alaparthi, Lakshmi; Lingam, Sneha; Younoszai, Zahra; Zheng, Li; Malik, Khatera S.; Younossi, Elena; Monge, Fanny; Hunt, Sharon L.; Goodman, Zachary; Younossi, Zobair M.
Abstract Background and Aim A significant number of autoantibodies have been reported in patients with non‐alcoholic fatty liver disease (NAFLD) patients. In the present study, our aim was to assess the role of disease and cell‐specific antibodies, namely anti‐adipocyte antibodies (anti‐AdAb) in patients with NAFLD and non‐alcoholic steatohepatitis (NASH). Methods Flow cytometry was used to detect the presence of anti‐AdAb (immunoglobulin M [IgM] and immunoglobulin G [IgG]) in sera from patients with biopsy‐proven NAFLD (n = 98) and in controls (n = 49) without liver disease. Univariate and multivariate analysis was performed to draw associations between anti‐AdAb IgM and IgG levels and the different clinical variables. Results Patients with NAFLD had significantly higher levels of anti‐AdAb IgM and significantly lower levels of AdAb IgG when compared with controls (P = 0.002 and P < 0.001, respectively). Patients with NASH had significantly higher levels of anti‐AdAb IgM when compared with non‐NASH NAFLD patients, P = 0.04. In multivariate analysis, anti‐AdAb IgM was independently associated with a higher risk for NASH (odds ratio[OR]: 2.90 [confidence interval (CI) 1.18–7.16], P = 0.02). Anti‐AdAb IgM was also found to be independently associated with portal inflammation in patients with NAFLD (OR: 3.01 [CI 1.15–7.90 P = 0.02]). Conclusions Anti‐AdAb IgM was independently associated with NAFLD and NASH while anti‐AdAb IgG was found to be protective against NAFLD. Anti‐AdAb IgM was found specifically to be associated with the inflammatory processes in NAFLD. These findings indicate that the anti‐AdAb IgM and IgG may play an immunomodulatory role in the pathogenesis of NAFLD and NASH.